2021
DOI: 10.1007/s00432-021-03849-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of single-site radiotherapy plus PD-1 inhibitors vs PD-1 inhibitors for oligometastatic non-small cell lung cancer

Abstract: Purpose Growing numbers of clinical trials test the efficacy of radiotherapy (RT) plus immune checkpoint inhibitors (ICIs), but the number of irradiated sites is not uniform. We aimed to evaluate the efficacy of single-site RT plus immunotherapy in oligometastatic non-small cell lung cancer (NSCLC) with smaller disease burdens and low tumor heterogeneity. Methods We retrospectively identified oligometastatic NSCLC (< 4 metastatic sites) patients treated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…After excluding 139 studies because the article type was not suitable for inclusion (including 13 case studies, 4 meta-analyses, 13 single-arm studies, 17 studies on other tumor types, 22 conference papers with abstracts only, 12 phase I studies, 15 ongoing studies, 42 reviews, and 1 comment), 3 RCTs and 12 NRCTs remained. A total of 15 clinical studies were reported in 16 publications ( Figure 1 ) ( Kataoka et al, 2017 ; Shaverdian et al, 2017 ; Tamiya et al, 2017 ; Fiorica et al, 2018 ; Theelen et al, 2019 ; Welsh et al, 2020 ; Hosokawa et al, 2021 ; Metro et al, 2021 ; Samuel et al, 2021 ; Sheng et al, 2021 ; Theelen et al, 2021 ; Öjlert Å et al, 2021 ; Guo et al, 2022 ; Qiang et al, 2022 ; Schoenfeld et al, 2022 ; Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding 139 studies because the article type was not suitable for inclusion (including 13 case studies, 4 meta-analyses, 13 single-arm studies, 17 studies on other tumor types, 22 conference papers with abstracts only, 12 phase I studies, 15 ongoing studies, 42 reviews, and 1 comment), 3 RCTs and 12 NRCTs remained. A total of 15 clinical studies were reported in 16 publications ( Figure 1 ) ( Kataoka et al, 2017 ; Shaverdian et al, 2017 ; Tamiya et al, 2017 ; Fiorica et al, 2018 ; Theelen et al, 2019 ; Welsh et al, 2020 ; Hosokawa et al, 2021 ; Metro et al, 2021 ; Samuel et al, 2021 ; Sheng et al, 2021 ; Theelen et al, 2021 ; Öjlert Å et al, 2021 ; Guo et al, 2022 ; Qiang et al, 2022 ; Schoenfeld et al, 2022 ; Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RT targets for three RCTs and five NRCTs were extracranial nonbrain metastases ( Tamiya et al, 2017 ; Fiorica et al, 2018 ; Theelen et al, 2019 ; Welsh et al, 2020 ; Hosokawa et al, 2021 ; Öjlert Å et al, 2021 ; Qiang et al, 2022 ; Schoenfeld et al, 2022 ). Three nonrandomized controlled studies included extracranial nonbrain metastases and intracranial brain metastases ( Shaverdian et al, 2017 ; Samuel et al, 2021 ; Wang et al, 2022 ). In three nonrandomized controlled studies, the RT targets included only brain metastases ( Metro et al, 2021 ; Sheng et al, 2021 ; Guo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding lung cancer studies, LCT-related adverse events were relatively more frequent when compared to other primaries, with grade 3 or higher rates ranging from 8% to 28.6%. Three studies reported the possibility of excessive grade 3 or higher adverse events related to LCT [ 28 , 35 , 67 ]. Grade 5 adverse event, potentially related to the LCT, occurred in three cases among seven lung cancer studies (3 of 281, 1.07%).…”
Section: Resultsmentioning
confidence: 99%
“… Forest plots of pooled analyses regarding progression-free survival, including all studies (A), studies with reliable comparability (B), and randomized controlled trials (C) [ 6 8 , 20 22 , 25 28 , 31 33 , 35 , 36 , 38 , 39 , 42 , 43 , 46 48 , 50 , 52 54 , 56 , 58 – 60 , 62 64 , 66 , 67 , 69 71 , 73 ]. HCC, hepatocellular carcinoma; H&N, head and neck; LCT, local consolidative therapy; NSCLC, non-small cell lung cancer; RCC, renal cell carcinoma; SCLC, small cell lung cancer; 5ySSFS, 5-year second-line systemic therapy free survival.…”
Section: Figmentioning
confidence: 99%
“…In the subgroup analysis of OS, sintilimab plus radiotherapy appeared to be beneficial in male patients, patients under 65 years old, and patients with less than 2 lines of previous systemic therapy. A study also suggested that in patients with oligometastatic NSCLC, single-site radiotherapy plus immunotherapy was more beneficial in patients with 1 to 2 metastases (28). There are still numerous questions about the impact of various radiotherapy dosage and methods on the magnitude of immune prognosis than conventional radiotherapy (29).…”
Section: Discussionmentioning
confidence: 99%